Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set: 73

Answer

$(z+2)(z-2)(z+3)(z-3)$

Work Step by Step

Step 1: Let $u=z^{2}$ $=u^{2}-13u+36$ Step 2: Factor $u^{2}-13u+36$ $=(u-4)(u-9)$ Step 3: Substitute back $u=z^2$ $=(z^{2}-4)(z^{2}-9)$ Step 4: Factor $z^{2}-4$ $=(z+2)(z-2)(z^{2}-9)$ Step 5: Factor $z^{2}-9$ $=(z+2)(z-2)(z+3)(z-3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.